ECCU Business Cycles : Impact of the U.S. - Sun, Yan (IMF Working Papers; Working Paper ;, 2009)
With a fixed peg to the U.S. dollar for more than three decades, the tourism-dependent Eastern Caribbean Currency Union (ECCU) countries share a close economic relationship with the U.S. This paper analyzes the impact of the United States on ECCU business cycles and identifies possible transmission channels. Using two different approaches (the common trends and common cycles approach of Vahid and Engle (1993) and the standard VAR analysis), it finds that the ECCU economies are very sensitive to both temporary and permanent movements in the U.S. economy and that such linkages have strengthened over time. There is, however, less clear-cut evidence on the transmission channels. United States monetary policy does not appear to be an important channel of influence, while tourism is important for only one ECCU country.